2009
DOI: 10.1590/s0037-86822009000400005
|View full text |Cite
|
Sign up to set email alerts
|

Experimental lagochilascariosis in X-chromosome-linked immunodeficient mice

Abstract: Lagochilascaris minor is the etiological agent of lagochilascariosis, a disease that affects the neck region and causes exudative abscesses, with eggs, adult parasites and L3/L4 larvae in the purulent exudates. Mice are now considered to be intermediate hosts for the parasite. To determine the pattern of infection in B1 cell-deficient mice, experimental lagochilascariosis was studied in BALB/c and X-chromosome-linked immunodeficient (xid) mice. BALB.xid-infected mice showed lower numbers of larvae. Third-stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In the same way, we denoted in a previous work that BALB/c infected mice produced IgM, IgA, IgG, and also IgE against the crude extract and mainly against secreted/excreted antigens of the parasite (Freitas et al, 2009). …”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In the same way, we denoted in a previous work that BALB/c infected mice produced IgM, IgA, IgG, and also IgE against the crude extract and mainly against secreted/excreted antigens of the parasite (Freitas et al, 2009). …”
Section: Discussionmentioning
confidence: 62%
“…Plates were read at 492nm on a Multiskan EX Labsystems. Cut-off value was determined by taking the mean OD of 24 control subjects plus three standards deviation (Freitas et al, 2009;Prudente et al, 2009b).…”
Section: Antibody Detectionmentioning
confidence: 99%
“…Spleen and lymph nodes had lymphoid follicles with expanded germinative centres. Cytokines were analysed in the serum of animals at 150 days post-infection because we demonstrated in a previous work that in this period it exists statistical differences in the number of larvae recovered and in the antibody levels of specific IgM, IgG and IgA between the two strains of mice (Freitas et al, 2009). Non-infected BALB/c (42.6 pg/ml) and BALB.xid (167 pg/ml) mice presented low level of sera IFN, though it was higher in the BALB.xid uninfected control animals (p = 0.01).…”
Section: Resultsmentioning
confidence: 99%
“…During this period, less severe pulmonary lesions and fewer subcutaneous nodules containing L3 larvae were observed in BALB/c mice than in C57BL/6 mice [ 12 ]. Moreover, we have recently demonstrated that both strains produce different classes of antibodies in response to crude extract and soluble antigens from the parasite [ 11 , 13 ].…”
Section: Introductionmentioning
confidence: 99%